A sodium-sulfur battery and a preparation method and application thereof
Patent Information
- Application Number
- CN202311373326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-10-23
AI Technical Summary
可溶性NaPS穿过隔膜扩散到Na阳极表面,容易产生严重的多硫化物穿梭效应,从而导致活性物质硫的损失
本发明通过构建异质结构来改善钠硫电池的氧化还原反应动力学,并展示出了其开发高性能钠硫电池的潜力。首先,本发明通过Na2SO4和Na2TeO3的简易碳热还原,将Na2S@Na2Te成功负载在碳基质中,充当钠硫电池的电极材料,Na2Te不仅可以作为成核位置以确保Na2S均匀分布在整个复合材料中,而且确保对钠硫电池的氧化还原反应具有显著的促进作用。此外,嵌入碳结构中的Na2S@Na2Te异质结构旨在有效抑制多硫化物的穿梭效应。本发明设计的Na2S/Na2Te@C具有丰富异质界面、高导电性和多孔性等优势,可以促进电子/离子扩散并提供高催化活性。通过引入Na2Te从本质上改善钠硫电池的Na2S正极电化学反应能力,同时,Na2Te的引入能有效降低钠硫电池中锂化和脱锂过程的能垒。此外,钠离子在Na2S中的扩散性能在Na2Te引入后也得到改善,这可能赋予Na2S基电池高倍率性能。最后,电化学研究还可以证实Na2Te引入可以显著降低氧化还原反应极化现象,表明钠硫电池的氧化还原反应动力学增强。
Smart Images

Figure CN117199497B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and more specifically, to a sodium-sulfur battery cathode material and its preparation method. Background Technology
[0002] As modern society's energy demands continue to rise, environmental pollution and resource depletion are becoming increasingly severe. To address these issues, extensive research into renewable resources has been a focus for decades. Through continuous development, the cost of generating electricity from renewable resources has decreased. However, integrating this electricity into reliable daily consumption remains a challenge. A key solution to these challenges is the use of rechargeable energy storage, such as battery technology.
[0003] Lithium-ion batteries, with their relatively higher energy density compared to other traditional electrochemical energy storage systems, have been widely used in various fields, such as mobile phones, electric watches, laptops, and even electric vehicles. However, for the past few decades, lithium-ion batteries have faced two key obstacles—high price and limited energy density—which have severely hampered their further development and large-scale application. Therefore, exploring alternative energy storage systems with abundant natural resources and ideal energy density is important and urgent to meet real-world needs.
[0004] Among emerging energy storage systems such as sodium-ion batteries, potassium-ion batteries, and lithium-sulfur batteries, sodium-ion batteries are one of the most promising alternatives to lithium-ion batteries, especially in large-scale energy storage applications. Due to the natural abundance of sodium ions and their similar intercalation chemistry to lithium-ion batteries, sodium ions are a suitable charge carrier from both a cost and chemical property perspective. Therefore, room-temperature sodium-ion batteries have also attracted considerable attention.
[0005] However, existing sodium-ion batteries also have many problems. First, Na... + The radius (0.98 Å) is greater than that of Li. + The large radius (0.69Å) leads to Na + The insertion / extraction and transport within the bulk material framework are kinetically slow, leading to a significant decrease in specific capacity and rate capacity. Secondly, Na... + The significant volume expansion caused by intercalation also leads to changes in the phase and lattice of the host material, which is detrimental to achieving excellent electrochemical stability. Furthermore, due to the low potential and large atomic mass of sodium, its specific energy is also lower than that of lithium-ion batteries, making the development of a host material with high specific energy for sodium storage a challenge.
[0006] Traditional sodium-ion battery cathode materials include layered transition metal oxides such as Na. xCathode materials such as MO2 (where M represents Fe, Co, Ni, and Mn), Prussian blue or white compounds coordinated with iron cyanide or manganese, and polyanionic vanadium-based phosphates or pyrophosphates are based on deintercalation reactions for charging and discharging. This results in unstable structures during the charging and discharging process, making them prone to irreversible phase transitions and low theoretical capacity.
[0007] Novel sodium battery systems based on redox reactions, such as sodium-sulfur batteries, show great promise as a good alternative to lithium-ion batteries. Sodium-sulfur batteries boast an extremely high theoretical capacity (1675 mAh g⁻¹). −1 Li, along with the Earth's abundant sodium and sulfur resources, is considered one of the promising next-generation energy storage systems and has received considerable attention. Furthermore, its high cost (>250 kg) is a significant factor. -1 Compared to limited resources (0.0018 wt% in the Earth's crust), metallic Na is cheaper (<5 kg). -1 ), and the content is more abundant (>2.5 wt% in the Earth's crust).
[0008] However, similar to the reaction mechanism of lithium-sulfur batteries, sodium-sulfur batteries also face rapid capacity decay during cycling, which severely limits their commercial application. This is mainly due to the low conductivity of sulfur and its discharge products Na₂S₂ / Na₂S, as well as the gradual dissolution of long-chain sodium polysulfides (NaPS) in the electrolyte. Soluble NaPS diffuses through the separator to the Na anode surface, easily generating a severe polysulfide shuttle effect, resulting in the loss of the active material sulfur.
[0009] In summary, existing sodium-sulfur batteries still have many limitations. Therefore, it is crucial to find an advanced sodium-sulfur battery cathode material with high specific capacity, high rate performance, excellent cycle stability, and good safety, which will promote the commercialization of sodium-sulfur batteries to a certain extent. Summary of the Invention
[0010] To address the above problems, the present invention aims to provide a sodium-sulfur battery cathode material and its preparation method.
[0011] To achieve the above objectives, the following technical solution can be adopted: a sodium-sulfur battery, the sodium-sulfur battery comprising: a positive electrode, an electrolyte, a separator and a negative electrode, wherein the chemical formula of the positive electrode material is Na2S / Na2Te@C.
[0012] The C mentioned is one of Ketjen black, carbon nanotubes, and graphene.
[0013] The method for preparing the sodium-sulfur battery, wherein the positive electrode material is prepared by the following method: anhydrous sodium sulfate, Na₂TeO₃, polyvinylpyrrolidone, and carbon material are dispersed in a solvent, and then the solution is stirred until there is no obvious precipitation. The solution is then dried to prepare a uniform powder; the positive electrode material is obtained by heat treatment under an oxygen-free atmosphere. The carbon material is one of Ketjen Black, carbon nanotubes, and graphene.
[0014] Drying includes two methods: rotary evaporation and spray drying.
[0015] The drying process is carried out at a temperature of 700–1100℃ for 4–12 hours.
[0016] Beneficial effects: This invention improves the redox reaction kinetics of sodium-sulfur batteries by constructing a heterostructure and demonstrates its potential for developing high-performance sodium-sulfur batteries. First, this invention successfully loads Na2S@Na2Te into a carbon matrix via a simple carbothermal reduction of Na2SO4 and Na2TeO3, serving as an electrode material for sodium-sulfur batteries. Na2Te not only acts as a nucleation site to ensure uniform distribution of Na2S throughout the composite material but also significantly promotes the redox reaction of sodium-sulfur batteries. Furthermore, the Na2S@Na2Te heterostructure embedded in the carbon structure aims to effectively suppress the shuttle effect of polysulfides. The Na2S / Na2Te@C designed in this invention possesses advantages such as abundant heterointerfaces, high conductivity, and porosity, which can promote electron / ion diffusion and provide high catalytic activity. The introduction of Na2Te fundamentally improves the electrochemical reaction capability of the Na2S cathode in sodium-sulfur batteries. Simultaneously, the introduction of Na2Te effectively lowers the energy barrier for lithiation and delithiation processes in sodium-sulfur batteries. Furthermore, the diffusion properties of sodium ions in Na₂S are improved after the introduction of Na₂Te, which may endow Na₂S-based batteries with high rate performance. Finally, electrochemical studies also confirm that the introduction of Na₂Te can significantly reduce redox polarization, indicating enhanced redox kinetics in sodium-sulfur batteries. Attached Figure Description
[0017] Figure 1 This is the XRD pattern of Na2S / Na2Te@C.
[0018] Figure 2 This is the XRD pattern of Na2S@C.
[0019] Figure 3 This is a SEM image of Na2S / Na2Te@C.
[0020] Figure 4 The graph shows the battery cycle performance of Na2S / Na2Te@C and Na2S@C at a current density of 0.1 C.
[0021] Figure 5 This is a graph showing the battery cycle performance of NFM at a current density of 0.1 C. Detailed Implementation
[0022] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0024] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.
[0025] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0026] In a first aspect, the present invention provides a sodium-sulfur battery cathode material, wherein the general chemical formula of the cathode material is Na2S / Na2Te@C.
[0027] The C mentioned is one of Ketjen black, carbon nanotubes, and graphene; Preferably, C is one of Ketjen black and graphene; More preferably, C is Ketjen Black.
[0028] This invention provides a sodium-sulfur battery cathode material, which is a Na2S / Na2Te@C composite material.
[0029] The preparation method includes the following steps: (1) Dispersing anhydrous sodium sulfate, sodium tellurite, polyvinylpyrrolidone and carbon materials in a suitable proportion in a mixed solvent of deionized water and ethanol, and then stirring the solution until there is no obvious precipitation; (2) The solution is then prepared into a uniform powder; the preparation method includes two methods: rotary evaporation and spray drying. (3) The obtained powder is subjected to continuous heat treatment at a certain temperature and for a certain time under an argon atmosphere, thus preparing the positive electrode material.
[0030] In a second aspect, the present invention provides a sodium-sulfur battery, the sodium-sulfur battery comprising: the positive electrode, electrolyte, separator and negative electrode described in the first aspect above; The electrolyte comprises: The solute in the electrolyte includes one or more of the following: sodium fluorophosphate (NaPF6), sodium fluoroborate (NaBF4), sodium tetraphenylborate (NaBPh4), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium perchlorate (NaClO4), sodium 4,5-dicyano-2-trifluoromethylimidazolium (NaTDI), and sodium 4,5-dicyano-2-pentafluoromethylimidazolium (NaPDI). Preferably, the solute in the electrolyte includes one or more of sodium hexafluorophosphate (NaPF6), sodium tetraphenylborate (NaBPh4), sodium bis(fluorosulfonyl)imide (NaFSI), and sodium bis(trifluoromethanesulfonyl)imide (NaTFSI). More preferably, the solute in the electrolyte is sodium bis(fluorosulfonyl)imide (NaFSI).
[0031] The solvent of the electrolyte includes one or more of the following: ethylene carbonate (EC), ethylene glycol dimethyl ether (DME), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), tetrahydrofuran (THF), triethylene glycol dimethyl ether (TDEM), tetraethylene glycol dimethyl ether (TEGDME), and vinylene carbonate (VC). Preferably, the solvent of the electrolyte includes one or more of ethylene carbonate (EC), ethylene glycol dimethyl ether (DME), propylene carbonate (PC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), and diethyl carbonate (DEC).
[0032] More preferably, the solvent of the electrolyte is dimethyl ethylene glycol (DME).
[0033] The diaphragm can be one of glass fiber diaphragm, ceramic diaphragm, or Celgard 2500 diaphragm; Preferably, the diaphragm is a ceramic diaphragm.
[0034] The sodium metal anode includes one of the following: sodium foil, sodium powder, sodium mesh, sodium alloy, carbon material, rechargeable sodium silicon material (NASICON), and oxide cathode material (NPF); The carbon materials include one of the following: natural graphite, expanded graphite, artificial graphite, glassy carbon, carbon fiber, hard carbon, soft carbon, activated carbon, porous carbon, carbon cloth, carbon paper, three-dimensional graphite, carbon black, carbon nanotubes, graphene, and modified materials of the above carbon materials. Preferably, the sodium metal anode comprises one of sodium foil, sodium powder, sodium mesh, and sodium alloy; More preferably, the sodium metal negative electrode is a sodium metal foil.
[0035] Example 1: (1) Preparation of Na2S / Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of Ketjen black were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then rotary evaporated into a uniform powder. The obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, thus preparing the cathode material.
[0036] Example 2: (1) Preparation of Na2S / Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of Ketjen black were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then sprayed into a uniform powder by spray drying. The obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, thus preparing the cathode material.
[0037] Example 3: (1) Preparation of Na2S / Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of carbon nanotubes were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation; the solution was then rotary evaporated into a uniform powder; the obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, and the cathode material was thus prepared.
[0038] Example 4: (1) Preparation of Na2S / Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of carbon nanotubes were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation; the solution was then sprayed into a uniform powder by spray drying; the obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, thus obtaining the cathode material.
[0039] Example 5: (1) Preparation of Na2S@Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of graphene were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then rotary evaporated into a uniform powder. The obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, thus preparing the cathode material.
[0040] Example 6: (1) Preparation of Na2S@Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of graphene were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then sprayed into a uniform powder by spray drying. The obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, thus preparing the cathode material.
[0041] Example 7: (1) Preparation of Na2S@Na2Te@C: 3.7 g of anhydrous sodium sulfate, 3.127 g of sodium tellurite, 1 g of polyvinylpyrrolidone (PVP) and 0.76 g of graphene were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then sprayed into a uniform powder by spray drying. The obtained powder was subjected to continuous heat treatment at 800 °C for 5 h under an argon atmosphere, thus preparing the cathode material.
[0042] Example 8: (1) Preparation of Na2S@C: 3 g of anhydrous sodium sulfate, 1 g of polyvinylpyrrolidone (PVP) and 0.672 g of Ketjen black were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then rotary evaporated into a uniform powder. The obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere to obtain the cathode material.
[0043] Example 9: (1) Preparation of Na2S@C: 3 g of anhydrous sodium sulfate, 1 g of polyvinylpyrrolidone (PVP) and 0.672 g of Ketjen black were dispersed in a mixed solvent of deionized water and ethanol, and the solution was stirred until there was no obvious precipitation. The solution was then sprayed into a uniform powder by spray drying. The obtained powder was subjected to continuous heat treatment at 800 °C for 9 h under an argon atmosphere, and the cathode material was thus prepared.
[0044] Electrochemical performance testing 1. Preparation of button-type sodium-sulfur batteries First, Na2S / Na2Te@C (Na2S@C), Super P and binder PVDF (mass ratio = 8:1:1) are ground evenly and dispersed in NMP solvent. Then, the mixture is continuously stirred into a slurry and coated onto carbon-containing aluminum foil. Finally, it is dried at 60 °C and the electrode sheet is cut into 10 mm diameter electrode sheets.
[0045] The battery assembly uses the prepared electrode sheet as the positive electrode, the sodium sheet as the negative electrode, and a ceramic membrane as the separator. The electrolyte is sodium bis(fluorosulfonyl)imide (NaFSI) dissolved in a ethylene glycol dimethyl ether solution with 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) additive. The specific preparation steps are as follows: NaFSI and DME (molar ratio = 1:1.2) are mixed and continuously stirred for 3 hours to prepare a transparent solution. Then, the prepared solution is diluted with the "inert" solvent TTE, which results in a decrease in viscosity, an increase in electronic conductivity, and an improvement in electrolyte wettability, thus preparing the electrolyte. Then, the battery is assembled in the following order: starting with the positive electrode shell, the assembly proceeds in the following sequence: positive electrode shell, positive electrode sheet, 40 μL electrolyte, separator, sodium sheet, gasket, spring sheet, and negative electrode shell, to obtain the CR2032 coin cell. The entire process is carried out inside a glove box.
[0046] 2. Electrochemical performance testing Constant current cycling and rate performance tests were conducted on a NEWARE BTS instrument manufactured by Shenzhen Newwell Electronics Co., Ltd., with a voltage range of 0.8–2.8 V.
[0047] Comparative Example 1: 1. Preparation of coin cell sodium-ion batteries First, NFM (NaNi) 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (a classic sodium-ion cathode material), Super P, and PVDF binder (mass ratio = 8:1:1) were ground uniformly and dispersed in NMP solvent, then continuously stirred into a slurry and coated onto carbon-containing aluminum foil. Finally, the mixture was dried at 60 °C and the electrode sheets were punched into 10 mm diameter electrode sheets. Battery assembly used the prepared electrode sheets as the positive electrode, the sodium sheet as the negative electrode, and a ceramic separator as the separator. The electrolyte was a 1 M NaPF6 Diglyme solution. Battery assembly was then performed in the following order: starting with the positive electrode shell, the assembly proceeded in the following sequence: positive electrode shell, positive electrode sheet, 40 μL electrolyte, separator, lithium sheet, gasket, spring sheet, and negative electrode shell, resulting in a CR2032 coin cell. The entire process was carried out inside a glove box.
[0048] 2. Electrochemical performance testing The constant current charge-discharge test in this study was conducted using a battery testing system (Shenzhen Xinwei Electronics Co., Ltd.), with a voltage range of 2-4 V. Electrochemical impedance spectroscopy (EIS) performance was tested using a CHI660E electrochemical workstation, with a frequency range of 100 kHz to 10 mHz and an AC amplitude of 5 mV.
[0049] like Figure 1 As shown in Figure 2, the successful preparation of Na2S / Na2Te@C and Na2S@C composite materials can be confirmed by X-ray diffraction. The XRD diffraction peaks of the obtained composite material Na2S / Na2Te@C correspond to the peak positions of the Na2S and Na2Te standard cards, indicating that the Na2S / Na2Te@C material was successfully prepared. After treatment without Na2TeO3 material in the reactants, only the Na2S peak was detected, and it corresponded to the Na2S standard card, indicating that Na2S@C was successfully prepared.
[0050] The structural advantages of Na2S / Na2Te@C can be clearly revealed using scanning electron microscopy (SEM). For example... Figure 3 As shown, the Na2S / Na2Te@C composite material consists of nanoparticles aggregated in secondary particles, interconnected to form a three-dimensional porous network. Furthermore, no significant aggregation of Na2S / Na2Te was detected on the carbon surface, indicating that Na2S / Na2Te is well distributed within the carbon matrix. The Na2S@C composite material was also prepared using a similar process to Na2S / Na2Te@C, except that it did not contain Na2TeO3 reactants.
[0051] like Figure 4 As shown in the figure, the battery with Na2S / Na2Te@C as the positive electrode and sodium sheet as the negative electrode exhibits a cycle life of over 150 cycles at a current density of 0.1 C. The figure also shows that the sodium-sulfur battery prepared in Example 1 has an initial discharge specific capacity of 651 mAh g⁻¹ at 0.1 C. -1 Furthermore, the discharge specific capacity remains at 590 mAh g after 150 cycles. -1 The discharge specific capacity retention rate was 91%, demonstrating good cycle stability. Furthermore, as shown in the figure, using Na2S@C as the electrode, the lack of Na2Te introduction cannot fully improve the electronic conductivity of the composite material, limiting the full utilization of sulfur and significantly reducing the battery capacity. In summary, the Na2S / Na2Te@C cathode material provided by this invention can significantly improve the conductivity of the composite material and effectively suppress the polysulfide shuttle effect, resulting in a sodium-sulfur battery exhibiting excellent cycle performance.
[0052] like Figure 5As shown, the NFM cathode material has an initial discharge specific capacity of 125 mAh g⁻¹ at 0.1 C. -1 Furthermore, the discharge specific capacity remains at 95 mAh g after 80 cycles. -1 The discharge specific capacity retention rate was 76%, indicating that the NFM cathode has poor cycle stability.
Claims
1. A sodium-sulfur battery, the sodium-sulfur battery comprising: A positive electrode, an electrolyte, a separator, and a negative electrode are characterized in that the chemical formula of the positive electrode material is Na2S / Na2Te@C; wherein C is one of Ketjen black, carbon nanotubes, and graphene; the positive electrode material is prepared by the following method: anhydrous sodium sulfate, Na2TeO3, polyvinylpyrrolidone, and carbon material are dispersed in a solvent, the solution is stirred until there is no obvious precipitation, and then the solution is dried to prepare a uniform powder; the positive electrode material is obtained by heat treatment under an oxygen-free atmosphere; wherein the carbon material is one of Ketjen black, carbon nanotubes, and graphene.
2. The method for preparing the sodium-sulfur battery according to claim 1, characterized in that, The cathode material is prepared by the following method: anhydrous sodium sulfate, Na2TeO3, polyvinylpyrrolidone and carbon material are dispersed in a solvent, the solution is stirred until there is no obvious precipitation, and then the solution is dried to prepare a uniform powder; the cathode material is obtained by heat treatment under an oxygen-free atmosphere.
3. The method for preparing a sodium-sulfur battery according to claim 2, characterized in that, Drying includes two methods: rotary evaporation and spray drying.
4. The method for preparing a sodium-sulfur battery according to claim 2, characterized in that, The drying process is carried out at a temperature of 700–1100℃ for 4–12 hours.
Citation Information
Patent Citations
Sodium-sulfur battery
JP1995335253A
Alkali metal secondary battery containing a dendrite-intercepting layer
US20160301078A1